2019
DOI: 10.1016/j.childyouth.2018.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical evidence on ethnic inequities in child welfare: Towards a research agenda

Abstract: This paper aims to compare developments in theory and evidence about ethnic disparities in the USA with findings from the Child Welfare Inequalities Project in England with a view to identifying key issues for a future research agenda. It has a particular focus on the relevance of the concept of the Hispanic Paradox for disparate intervention rates between ethnic populations in England. Three key theoretical dimensions for explaining such disparities are identified and outlined: artefactual, demand and supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…However, the interaction between the projectors that affect the overall health of a child is yet to be accessed. For instance, health-seeking behaviour by guardians for their children is affected by multiple of factors such as socio-demographic characteristics, issues related to health services, social, cultural and economic factors as confounding factors that in uence the outcome of the health of the child [40,49]. Similarly, guardians' sociodemographic characteristics are also in uenced by social, cultural and economic factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interaction between the projectors that affect the overall health of a child is yet to be accessed. For instance, health-seeking behaviour by guardians for their children is affected by multiple of factors such as socio-demographic characteristics, issues related to health services, social, cultural and economic factors as confounding factors that in uence the outcome of the health of the child [40,49]. Similarly, guardians' sociodemographic characteristics are also in uenced by social, cultural and economic factors.…”
Section: Discussionmentioning
confidence: 99%
“…These ethnic groups do not mirror the social positions of African-American and Latino populations in the USA, because of the two countries’ very different histories, but the Asian and Black groups represent the two main ethnic minority categories in England and Wales and there are some similarities to those US minority populations in terms of their contact with child welfare systems. 9…”
Section: Methodsmentioning
confidence: 99%
“…8 We also see from ecological studies that there is a concentration of protective interventions in deprived neighbourhoods. 9,10 Research in the United States by Eckenrode, Smith, McCarthy and Dineen 11 found that both income inequality and child poverty rates were associated with higher substantiated child maltreatment rates at the county level. Income inequality was measured by using Gini coefficients 12 and control variables included child poverty, adult qualifications and ethnic diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The history of social work tells us that good intentions regarding justice and rights are no guarantee of good outcomes. Recent evidence that a child in Scotland is three or four times more likely to be in out-of-home care than a similar child in Northern Ireland, or that a child of Indian heritage in England is 20 times less likely to be in foster or residential care than a child of Black African-Caribbean parents, leaves no room for complacency about the forms and consequences of current policy and practice (Bywaters et al 2018a(Bywaters et al , 2018b). An inequalities perspective acts as a reality check on the outcomes of well-intentioned policy, practice, and service provision.…”
mentioning
confidence: 99%